2020
DOI: 10.1111/dme.14264
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of randomized controlled trials of psychological interventions to improve glycaemic control in children and adults with type 1 diabetes

Abstract: AimWe conducted a systematic review aggregate and network meta-analysis of psychological interventions for people with type 1 diabetes to assess their effectiveness in improving glycaemic levels. Abstract International. We included randomized controlled trials (RCT) of psychological interventions for children and adults with type 1 diabetes reported in any language. We extracted data on publications, participant characteristics at baseline, intervention and control group, and data for the primary outcome, chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
3
22
1
1
Order By: Relevance
“…The findings of the current meta-analysis further support the benefits of applying CBT-based interventions in the management of DM. Our results are different from previous meta-analysis which showed CBT had small effect on HbA1c, that CBT-based interventions have moderate effect size on glycaemic control ( 7 ). It is possible we have bigger number of studies than previous studies which may have generate more power than the published study ( 7 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of the current meta-analysis further support the benefits of applying CBT-based interventions in the management of DM. Our results are different from previous meta-analysis which showed CBT had small effect on HbA1c, that CBT-based interventions have moderate effect size on glycaemic control ( 7 ). It is possible we have bigger number of studies than previous studies which may have generate more power than the published study ( 7 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The aggregate meta-analysis did not find reduction in HbA1c for children or adults. While, the network meta-analysis for adults showed that CBT-based interventions have potential positive effects on HbA1c reduction ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This improvement in glycemic control was comparable with other studies of psychological treatments to support diabetes self-management. 33 An RCT of face-to-face CBT conducted by the same investigators observed a reduction in HbA1c of 5.5 mmol/mol. 13 Our findings are comparable with those of a feasibility RCT for people with type 1 and type 2 diabetes comparing an online CBT program with therapist support provided by phone and email versus treatment as usual for depression, 21 although the difference was that our inclusion criterion was suboptimal glycemic control, whereas in that study it was depressive symptoms and they included type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions use didactic and enhanced learning methods to improve self-management of diabetes by reducing identi able gaps in knowledge [25]. Psychological therapies use the therapeutic alliance between patient and therapist, in which the patient's problems are understood in terms of emotions, cognitions, and behaviors [26], yet, psychological interventions have not proven effective on glycated hemoglobin (HbA1c) in people with type 1 [27] or type 2 diabetes [22]. Health educational tools that aim at translating person-centered care into practice and nding ways to enhance intrinsic motivation may lead to greater long-term behavior change than tools solely relying on external motivation [28].…”
Section: Description Of the Interventionsmentioning
confidence: 99%